Peningkatan Hasil Belajar Pendidikan Pancasila Berbantuan Canva Berbasis Problem Based Learning di Kelas V SDN 04 Tarandam Kota Padang - Hamida Azzahra; Desyandri; Yeni Erita; Muhammadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning outcomes of students in class V of SDN 04 Terandam, Padang City. This is due to the lack of active involvement of students in the learning process because learning is still teacher-centered, low critical thinking skills and self-confidence in expressing opinions and discussing with peers or groups. This research aims to describe the improvement in learning outcomes of Canva-assisted Pancasila Education using the Problem Based Learning model in class V of SDN 04 Terandam, Padang City. This type of research is Classroom Action Research (PTK) using 2 types of approaches, namely qualitative and quantitative approaches. This research was carried out in 2 cycles, cycle I consisted of 2 meetings and cycle II consisted of 1 meeting which was carried out in four stages, namely planning, implementation, observation and reflection. The subjects of this research were teachers and students of class V at SDN 04 Terandam, Padang City, totaling 15 people. The research results showed that the RPPM aspect in cycle I obtained an average of 87.5% (B), increasing in cycle II to 95% (A). In the activity aspect, teachers in cycle I obtained an average of 85.5% (B), increasing in cycle II to 95% (A). In the activity aspect, students in cycle I obtained an average of 85.5% (B), then increased in cycle II to 95% (A). The learning outcomes of students in cycle I obtained an average of 73.5 (D), and increased in cycle II to 86 (B). It can be concluded that the Problem Based Learning model can improve the learning outcomes of Pancasila education in class V of SDN 04 Terandam, Padang City. Keywords: Learning outcomes, Pancasila Education, Canva, Problem Based Learning.